The Effect of Job Burnout Stability (Applied Study on the Health Sector in Asir Region in KSA- 1444AH) - Al-Shehri, Asma Mohamed; Abo Dahesh, Reem Awad; Al Sultan, Sara Hussein; Asiri, Bayan Abdullah; Al-Maliki, Jamilah Salman (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aims to identify the effect of job burnout on job stability: an applied study on the health sector in Asir region, and used the descriptive and analytical method that it is concerned with studying the phenomenon as it exists in reality, by collecting data about it, classifying it, organizing it and expressing it in order to reach conclusions or generalizations that help in Developing the reality that is being studied, and the study population consists of all workers in the health sector in Asir region, and a simple random sample consisting of (400) employees who belong to the study community was chosen, and the study reached a set of results that the level of responses of the study sample individuals indicated that there is a feeling of exhaustion The respondents emphasized that humanity within the health sector came to a weak degree, and it was found that personal achievement was of a weak degree, and it was found that job stability in the health sector in Asir region was of a medium degree, and finally - that there is a relationship between (emotional exhaustion and humanity Personal achievement) and career stability. The study resulted in a set of recommendations to improve the salaries of workers in the health sector, employ more working staff, especially practitioners, motivate employees financially and morally, and establish a special committee concerned with public relations between workers, and reduce the workload of workers, especially practitioners, flexibility in work, without Interferes with the workflow.